A Maturity Model for Implementing ITIL V3 in Practice - Pereira, R.; Mira da Silva, Miguel (2011 IEEE 15th International Enterprise Distributed Object Computing Conference Workshops, 2011)
ITIL is the most popular "best practices" framework for managing Information Technology (IT) services. However, implementing ITIL is not only very difficult but also there are no recommendations and guidelines for it. As a result, ITIL implementations are usually long, expensive and risky. In a previous paper we proposed a maturity model to assess an ITIL implementation and provided a roadmap for improvement based on priorities, dependencies, and guidelines. In this paper, we demonstrate a practical application of the proposed model with a questionnaire to assess the Incident Management and Configuration management processes as well as the Service Desk Function. We evaluate the questionnaires in 13 assessments in five Portuguese organizations and then implemented a prototype to support the assessments. We finally draw conclusions that could be very useful for organizations that are considering ITIL implementation.